PENGARUH METODE SQ3R TERHADAPKEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGRI 08 PALEMBANG - Sari Putri Ramanda; M. Taheri Akhbar; Bambang Hermansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of using the SQ3R method on the reading comprehension ability of fourth grade students of SDN 08 Palembang. This study is a quantitative experimental type with one pretest and posttest design. The population and sample of this study were all fourth grade students of SDN 08 Palembang. The sample selection technique used was Total Sampling. Data collection techniques in this study were observation and testing. Data analysis used the paired sample t-test. The results of this study indicate that there is an effect of the SQ3R method. This result is evidenced by the average value of 81.69 with a good category. And based on the results of the t-test calculation (paired sample t-test) a significant value (2-tailed) of 0.000 was obtained. Because the significant value (probability) is less than 0.05, the results of the paired samples t-test show that there is a significant difference Ho is rejected and Ha is accepted. This shows that there is an effect of using the SQ3R method on students' reading comprehension abilities.